Pengaruh Penggunaan Metode Cooperative Script terhadap Keterampilan Menulis Narasi pada Muatan Bahasa Indonesia - Dewi, Lulu Luciana; Simbolon, Marlina Eliyanti (Kamboti Journal of Education Research and Development, 2021)
This research is motivated by the low writing skills in Indonesian subjects caused by students who think that writing skills are very difficult to do and students have difficulty finding ideas or ideas that are in accordance with the written discourse. This study aims to determine the effect of the Cooperative Script learning model on the narrative writing skills of fifth grade students on the Indonesian language content at SDN 3 Awirarangan. The research method used is pre-experimental with one group pretest posttest design. The independent variable in the research is the cooperative script learning method and the dependent variable in the research is the narrative writing skill. The subjects in this study were all the fifth grade students of SDN 3 Awirarangan totaling 26 students. The data collection technique used a narrative writing test. Data analysis techniques used are normality test and hypothesis testing. Based on the results of the data the average value of students at the time of the pretest was 50 and the average value of the posttest was 79.42, indicating that the average value of students was different between the average value of the pretest before being given treatment and the average value of the posttest after being given treatment. . This is evidenced by the t-test with a significance level of = 5% obtained tcount of 8.28 and the results of ttable 2.06, then tcount (8.28) > ttable (2.06). This states that H1 is accepted and H0 is rejected. Thus, it can be concluded that there is an influence of the cooperative script learning model on the narrative writing skills of fifth grade students on the Indonesian language content at SDN 3 Awirarangan.